Upaya Perlindungan Korban Pemerkosaan Anak Di Bawah Umur Oleh DPPKBP3A Di Kota Tasikmalaya - Adelia, Dilla; Nasril, Puji Fauzia (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
abstract. Cases of rape of minors in Tasikmalaya City have increased so that this city is categorized as a child protection emergency city with the highest case in 2019 with 14 victims. The purpose of this study was to determine the efforts to deal with victims of rape cases. This research uses a qualitative method with an empirical approach by conducting interviews and observations at the Office of Population Control, Family Planning, Women's Empowerment and Child Protection (DPPKBP3A). The result of this study is that the handling of cases of rape of minors is not only limited to the Office of Women and Child Protection (DPPKBP3A), but can be done effectively at the Police or the Regional Child Protection Commission (KPAD) by providing psychologist assistance to victims. Keywords: Efforts, Protection, Child Rape.